Swimming into the Open. Issue 150 (June 2016) - Drayton, Brendaly; Rosser‐Mims, Dionne; Schwartz, Joni; Guy, Talmadge C.
Abstract : This concluding chapter discusses the important contribution Black men's voices have made and can make to adult education theory and practice. Particular emphasis is placed on troubling the various factors that contribute to the silencing of those voices.